Beyond a Nature-inspired Lotus Surface: Simple Fabrication Approach Part I. Superhydrophobic and Transparent Biomimetic Glass Part II. Superamphiphobic Web of Nanofibers - Lim, Hyuneui (IntechOpen, 2011)
None